2001
DOI: 10.1097/00005392-200110000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Randomized Trial Comparing Shock Wave Lithotripsy and Ureteroscopy for Management of Distal Ureteral Calculi

Abstract: Ureteroscopy and shock wave lithotripsy were associated with high success and low complication rates. However, shock wave lithotripsy required significantly less operating time, was more often performed on an outpatient basis, and showed a trend towards less flank pain and dysuria, fewer complications and quicker convalescence. Patient satisfaction was uniformly high in both groups. Although ureteroscopy and shock wave lithotripsy are highly effective for treatment of distal ureteral stones, we believe that HM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
45
1
8

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(56 citation statements)
references
References 22 publications
2
45
1
8
Order By: Relevance
“…Most of the comparative studies between ESWL and ureteroscopy are not conclusive and sometimes ambiguous. While some studies are in favor of ESWL [7], others concluded that ureteroscopy is the preferable approach [16][18]. We compared several objective outcomes of each procedure method, including stone clearance rate, treatment time, procedural time, complications and costs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the comparative studies between ESWL and ureteroscopy are not conclusive and sometimes ambiguous. While some studies are in favor of ESWL [7], others concluded that ureteroscopy is the preferable approach [16][18]. We compared several objective outcomes of each procedure method, including stone clearance rate, treatment time, procedural time, complications and costs.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple sessions of ESWL resulted in a similar outcome to ureteroscopy. This could explain why the stone clearance rate of ESWL varied from 80%–100% [4], [7]. Furthermore, the stone clearance rate of ESWL was determined by stone composition and stone hardness.…”
Section: Discussionmentioning
confidence: 99%
“…Another notably observed point was that the success rate in the f irst session of lithotripsy was 89.5% and only 10.5% of subjects required additional sessions of treatment. In contrast, some previous studies have reported that successful treatment required more than a single-session lithotripsy (Pearl , 2001). Interestingly, a considerable number of our considered patients with the urinary calculi in the lower segment of their ureters.…”
Section: Resultsmentioning
confidence: 90%
“…Ghimire et al(2012) reported that the number of sessions needed for lithotripsy increased as the location of the stones moved from proximal part of the ureter to the distal part. Specif ically, 1.11 and 1.71 sessions were required for stones in the upper and lower ureter, respectively (Pearl et al, 2001). However, our study revealed the number of sessions were less and most of the patients responded to one session of lithotripsy only.…”
Section: Discussionmentioning
confidence: 99%
“…Perchel ve ark. [28,29] Üreter taşlarının tedavisinde URS'de kullanılan farklı enerji kaynakları ile yüz güldürücü sonuçlar elde edilmiştir. Kara ve ark.…”
Section: Discussionunclassified